Identification of key odorants related to the typical aroma of oxidation-spoiled white wines - Ferreira, António César Silva (2011)
The oxidative degradation of white wines rapidly leads to a loss of their sensorial qualities. The identification of the most important descriptors related with oxidation-spoiled wine was performed by a trained sensory panel. The terms selected were “honey-like”, “farm-feed”, “hay”, and “woody-like”. By gas chromatography−olfactometry analysis three aromatic zones related to these descriptors in the oxidation-spoiled white wines could be determined. Comparison of the aroma extract dilution analysis aromagrams of oxidation-spoiled white wines and a nonspoiled wine showed the highest values of dilution factors were attributed to 3-(methylthio)propionaldehyde, phenylacetaldehyde, 1,1,6-trimethyl-1,2-dihydronaphthalene (TDN), and 4,5-dimethyl-3-hydroxy-2(5H)-furanone (sotolon). A “forced aging” experiment was implemented to simulate the typical oxidation-spoiled aroma. Samples rated with the highest score in the ranking test were also those that presented the highest concentration of these four molecules. To test the sensory impact of these substances, a normal wine (unspoiled) was spiked with these molecules (with the exception of TDN) singly and in combination, and the similarity value (SV) between samples and the oxidation-spoiled white wines was then determined. The highest value from the similarity tests was 5.4 when the three compounds were added simultaneously; 3-(methylthio)propionaldehyde alone was found to be responsible for 3.6, suggesting that, among the molecules studied, it is the most important contributor to the typical aroma of an oxidation-spoiled white wine.